Opioid Endocrinopathy - Demarest, Susan P.; Gill, Ranjodh S.; Adler, Robert A. (Endocrine practice, 2015)
The use of prescription opioids has increased dramatically over the past 20 years. Opioids appear to affect multiple endocrine pathways leading to abnormal levels of different hormones such as testosterone, cortisol, and prolactin (PRL). In this article, we review the current data regarding opioid effects on the hypothalamus, pituitary, and bone metabolism. We conducted a PubMed search for articles regarding opioids and each of the following subjects: testosterone, estrogen, cortisol, thyroid, growth hormone (GH), and bone. Most articles were primary source studies conducted between 1980 and 2014. Articles were included if studies were conducted within the time period, published in English, and available as full-length articles. Case reports were reviewed, but controlled studies were given more weight. Opioids appear to affect each of the pituitary hormone pathways in addition to altering bone metabolism. The most commonly reported and substantial effect was hypogonadism in both sexes; however, suppression of the adrenal axis may be more common than initially thought. Although some studies report a change in thyroid and GH levels, overall effects have not been thoroughly studied. There is some evidence for increased fracture risk, possibly mediated by hypogonadism and fall risk. More research is needed to determine which opioids are more likely to cause endocrine dysfunction and which patients need to be screened and treated. Also unknown is the length of time to the development of hormonal changes after starting opioid therapy and if cessation of opioid therapy can normalize hormone levels.